NET ASSET VALUE GROWTH OF CONVENTIONAL FIXED INCOME MUTUAL FUNDS AND INFLATION IN 2021-2023 - Purnamasari, Puji Endah; Sartika, Farahiyah (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2024)
Mutual funds are a form of investment for people who have capital to invest in the capital market through the management of investment managers in the form of a securities portfolio. Mutual funds are divided into 4 (four) categories, namely equity, mixed, fixed income and money market mutual funds. Net Asset Value (NAV) is a measurement for the performance of fixed income mutual funds. Some factors that can affect the NAV value are exchange rates, interest rates and inflation. The purpose of this study is to determine and analyze the effect of BI Rate and exchange rate on NAV in Indonesia (2021-2023 period) moderated by inflation. This type of research is quantitative description with time series data. Research data testing using the help of SPSS Statistics software with secondary data types. This research was tested using the Calculation Assumption Test, Multiple Regression Analysis using Moerated Regression Analysis (MRA) and Hypothesis Testing. The results showed that BI Rate has a positive effect on NAV, this is because public interest in mutual funds is influenced by interest rates. The exchange rate in the study did not have a significant effect, this is because fixed income mutual funds are long-term investments and the NAV value is stable so that exchange rate fluctuations do not really affect the NAV value. While inflation is able to moderate the relationship between BI Rate and NAV as Quasi Moderation, this is because many strategies are used to protect the value against inflation, one of which is long-term investment in the form of securities and a fairly stable return. However, inflation is not able to moderate the relationship between the exchange rate and NAV, this is because the depreciation of the rupiah is not followed by changes in the investment portfolio, especially in mutual fund investment.